2012
DOI: 10.1586/era.11.187
|View full text |Cite
|
Sign up to set email alerts
|

Use of pegylated liposomal doxorubicin in the management of platinum-sensitive recurrent ovarian cancer: current concepts

Abstract: Pegylated liposomal doxorubicin (PLD) was first approved for platinum-refractory ovarian cancer in 1999 and then received full approval for platinum-sensitive recurrent disease in 2005 by the US FDA. PLD remains an important therapeutic tool in the management of recurrent ovarian cancer in 2012. Phase-II and III clinical trials of single-agent PLD in patients with platinum-sensitive recurrent ovarian cancer have reported overall mean survival times up to 29 months. Recent interest in PLD/carboplatin combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
0
7
0
1
Order By: Relevance
“…In this context, we propose that our findings may be relevant in the treatment of cancers such as breast and ovarian cancers, particularly in older women, because the consumption of a calcium‐rich diet or a dietary supplement that counteracts osteoporosis (Turck ) could alter the efficacy of doxorubicin, a commonly used chemotherapeutic (Rakowski et al . ; Lao et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, we propose that our findings may be relevant in the treatment of cancers such as breast and ovarian cancers, particularly in older women, because the consumption of a calcium‐rich diet or a dietary supplement that counteracts osteoporosis (Turck ) could alter the efficacy of doxorubicin, a commonly used chemotherapeutic (Rakowski et al . ; Lao et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, PEGylated-liposomal doxorubicin (Doxil) was characterized by a very long circulating half-life, favorable pharmacokinetic behavior and specific accumulation in tumor tissues compared with conventional liposomal doxorubicin or free doxorubicin [110,111]. Numerous liposomal drug formulations containing chemotherapeutic agents, antisense-oligodeoxynucleotides, siRNA, deoxyribonucleic acid (DNA), or radioactive particles that can target multiple signaling pathways are in various stages of development [71,92,112].…”
Section: Use Of Nanotechnology To Develop Mtismentioning
confidence: 99%
“…In addition, it was suggested that PLD had a more favorable toxicity profile than CϩP [7], but these findings were not always corroborated in other clinical trials [9,11]. There is a need to clarify the efficacy and toxicity profiles of CϩPLD compared with CϩP in order to facilitate therapeutic decision making and optimize patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent clinical trials suggest that combination therapy consisting of carboplatin with PLD (CϩPLD) may have similar or better rates of progression-free survival (PFS) and similar overall survival (OS) when compared with CϩP, the current first-line regimen [7][8][9][10]. In addition, it was suggested that PLD had a more favorable toxicity profile than CϩP [7], but these findings were not always corroborated in other clinical trials [9,11]. There is a need to clarify the efficacy and toxicity profiles of CϩPLD compared with CϩP in order to facilitate therapeutic decision making and optimize patient outcomes.…”
Section: Introductionmentioning
confidence: 99%